Is there a gender bias in intergenerational mobility? Evidence from Cameroon - Rose Fontep; Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
We examine the intergenerational mobility of women relative to men, using paired mother-daughter and father-son data on occupation and education for Cameroon. We find that both in occupation and education, intergenerational mobility is higher for sons than for daughters. The intergenerational transmission of occupation is particularly strong for women in low-paid occupations as compared with men. In the case of educational mobility, the effect of the mother's education on the daughter's education is strongest at the post-primary levels. Our results suggest that there is strong gender bias in intergenerational mobility, and that public policies need to alleviate the inequality of opportunity faced by women relative to men. The results for both occupational mobility and educational mobility do not substantially change when we control for circumstances in which both daughters and sons are born to the same parents, or in which children and parents are living in the same household.
Keywords: J6; J62; O12; 330; occupational mobility; educational mobility; intergenerational mobility; gender; Cameroon